2013
DOI: 10.4161/bioe.23041
|View full text |Cite
|
Sign up to set email alerts
|

Naturally selecting solutions

Abstract: For decades, computer scientists have looked to nature for biologically inspired solutions to computational problems; ranging from robotic control to scheduling optimization. Paradoxically, as we move deeper into the postgenomics era, the reverse is occurring, as biologists and bioinformaticians look to computational techniques, to solve a variety of biological problems. One of the most common biologically inspired techniques are genetic algorithms (GAs), which take the Darwinian concept of natural selection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…[99][100][101][102][103][104][105][106][107] Indeed, this changing focus allowed me to establish links with the Department of Computing at Cork Institute of Technology (CIT). 108,109 This union produced CIT's first commercial spinout company, nSilico, which I co-founded in 2012. Combining all of the above elements, I wrote and coordinated ClouDx-i, a €1.3 million EU FP7 funded project, with CIT, nSilico and the University of Edinburgh as partners.…”
Section: In Silico Diagnosticsmentioning
confidence: 99%
“…[99][100][101][102][103][104][105][106][107] Indeed, this changing focus allowed me to establish links with the Department of Computing at Cork Institute of Technology (CIT). 108,109 This union produced CIT's first commercial spinout company, nSilico, which I co-founded in 2012. Combining all of the above elements, I wrote and coordinated ClouDx-i, a €1.3 million EU FP7 funded project, with CIT, nSilico and the University of Edinburgh as partners.…”
Section: In Silico Diagnosticsmentioning
confidence: 99%
“…When the evaluation is completed, a selection is performed to select their shortest average. Selecting about 40% of the objects and creating the remaining 60% through other operations is efficient for navigation [35,36]. Considering the possibility that the best solutions in the group are reasonable solutions, 5% of the fittest individuals are selected as those with the shortest average latency in the group.…”
Section: Evaluation and Selectionmentioning
confidence: 99%
“…Many mutations in the next generation of topology synthesis cases can cause the solution to converge too late and unnecessarily increase computation time. Other GA studies have shown that obtaining mutation-generated cases is less than 10% of all cases [35,36]. In this study, we set this ratio to 10%.…”
Section: Mutationmentioning
confidence: 99%
“…GAs are evolution-inspired metaheuristics that allow to optimize populations of individuals [14]. Such evolutionary approaches were successfully applied to various biological questions [12], e.g., design of synthetic networks and, in particular, design of single-circuit classifiers [26,16]. Due to the high flexibility of GAs in terms of design and parameters, the algorithm may be efficiently adapted to the distributed classifier problem.…”
Section: Introductionmentioning
confidence: 99%